CONTROL OF THE TWO DoF INVERTED PENDULUM - M. Fajar (Dinamika Teknik Mesin, 2014)
This paper describes how to simulate and control the two DoF inverted pendulum system, a dynamics of multibody system. The control strategy used is based on the conventional feedback method for the stabilisation of the two DoF inverted pendulum system. Simulation study has been done shows that conventional method i.e. pole placement control strategy is capable to control multi input and multi output of the two DoF inverted pendulum system successfully. The result shows that pole placement control strategy gives satisfactory response that is presented in time domain.